Plan exportador para la evaluación del mercado aguacate hass, a favor de la empresa avocados export, ubicada en el departamento del Tolima. (2021)
The present investigation focuses on the search and analysis of an objective market for the export of Avocado Hass produced by the Avocados Export company, for this a variety of data were analyzed that allowed to determine that the United States is the country that greater benefits grants to An export process. Within this process, the present presentation D different variables that will allow the exporter to know how the international market is located and what are the opportunities for their product. Likewise, a financial analysis was performed that resulted in the feasibility of the project based on information provided by the company and statistics of international trade. Finally, it is concluded that the company has great possibilities to position their product in the North American market